Editing the Central Nervous System Through CRISPR/Cas9 Systems - Cota-Coronado, Agustin; Díaz-Martínez, Néstor Fabián; Padilla-Camberos, Eduardo; Díaz-Martínez, N. Emmanuel (Frontiers in Molecular Neuroscience, 2019)
The translational gap of treatments based on gene therapy has been shortened in recent years, due to the improvement of gene editing tools such as the CRISPR/Cas9 system and its variations. This has allowed the development of more precise therapies for neurodegenerative diseases, where access is privileged, therefore the engineer of complexes that can access the Central Nervous System (CNS), with the least possible inconvenience are fundamental. In this review we describe current alternatives to generate systems based on CRISPR/Cas9, which can cross the Blood Brain Barrier (BBB) and be possibly use further in the clinical area for improve neurodegeneration in Parkinson’s and Alzheimer disease.